Mitigating conflict between human and long-tailed macaque in Balun Ijuk Village, Bangka Regency - Randi Syafutra; Ririn Apriyani; Fatmawati Fatmawati; Reani Febriyani; Muhammad Yulio Gempa Sakti; Aji Kurbiyanto (Community Empowerment, 2023)
Negative interactions between humans and wildlife, as well as a decrease in the quality of wildlife habitat, can result in conflicts between humans and wildlife. Under certain conditions, this conflict can be detrimental to all parties involved. This Community Service (CS) project aimed to increase people’s knowledge and improve their attitude and perception towards the long-tailed macaque in Balun Ijuk Village. The project utilized three methods in stages: (1) Unstructured Interview, (2) Focus Group Discussion (FGD), and (3) Socialization. Ultimately, this CS project had a positive impact by increasing knowledge and improving the attitude and perception of the people towards the long-tailed macaque in Balun Ijuk Village.